2019
DOI: 10.1002/cmdc.201900608
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of in vitro Assays for Predicting the Nonspecific Binding of PET Imaging Agents in vivo

Abstract: Nonspecific binding (NSB) is a key parameter in optimizing PET imaging tracers. We compared the ability to predict NSB of three available methods: LIMBA, rat fu,brain, and CHI(IAM). Even though NSB is often associated with lipophilicity, we observed that logD does not correlate with any of these assays, clearly indicating that lipophilicity, while influencing NSB, is insufficient to predict it. A cross‐comparison of the methods showed that all three correlate and are useful predictors of NSB. The three assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
(40 reference statements)
2
14
0
Order By: Relevance
“…On top of its significant role in mediating brain penetration, lipophilicity, frequently approximated by logD measurements, is an important metric in the context of PET tracer development as it allows for the preliminary assessment of the extent of NDB to be expected. While the correlation of logD and NDB is weak at best [ 14 , 15 ], certain hard lipophilicity cutoffs, e.g., shake-flask logD < 3.5, continue to be successfully employed in PET tracer development [ 16 ]. However, the design of brain-penetrable PET tracers displaying low NDB is a multiparameter optimization effort: relying too much on individual physicochemical parameters may be misleading since it does not give a full picture.…”
Section: Resultsmentioning
confidence: 99%
“…On top of its significant role in mediating brain penetration, lipophilicity, frequently approximated by logD measurements, is an important metric in the context of PET tracer development as it allows for the preliminary assessment of the extent of NDB to be expected. While the correlation of logD and NDB is weak at best [ 14 , 15 ], certain hard lipophilicity cutoffs, e.g., shake-flask logD < 3.5, continue to be successfully employed in PET tracer development [ 16 ]. However, the design of brain-penetrable PET tracers displaying low NDB is a multiparameter optimization effort: relying too much on individual physicochemical parameters may be misleading since it does not give a full picture.…”
Section: Resultsmentioning
confidence: 99%
“…The data in Table 2 revealed that both radioligands had a high PPB level, but [ 18 F]F-IV is associated with proteins to a greater extent than [ 11 C]MPbP: >98 vs. 92% for rats and >99 vs. 98% for humans, respectively. The measured high PPB of [ 18 F]F-IV appears to be responsible for the high level of radioactivity in the blood, its retention in rat tissues, and for lower brain uptake (compared to MPbP) in LPS-treated rats, [34]. In this study, we did not evaluate the contribution of non-specific binding or off-target interactions of [ 18 F]F-IV with proteins and phospholipids in the brain.…”
Section: Plasma Protein Binding (Ppb) For [ 18 F]f-iv and [ 11 C]mpbpmentioning
confidence: 91%
“…Bearing the potential application of the designed carbamates as central nervous system PET tracers in mind, we opted to evaluate selected physico-chemical properties, such as lipophilicity, serving as approximate surrogate measures of NDB and blood-brain bar rier (BBB) permeability. Although the predictive power of, for example, logP or logD, for NDB or BBB penetration is critically debated, their influence on the aforementioned phe nomena is undisputed [26][27][28][29].…”
Section: Physico-chemical Property Profile and Stabilitymentioning
confidence: 99%